AB0569 Markers of Subclinical Cardiovascular Disease in Behcet's Disease: Correlations with Demographic and Clinical Profile. (10th June 2014) - Ferrari, C.; Talarico, R.; Stagnaro, C.; Barsotti, S.; Neri, R.; d'Ascanio, A.; Di Lascio, N.; Bianchini, E.; Morales, M.A.; Bombardieri, S.
Abstract : Background: Growing interest exists on the role of markers of subclinical cardiovascular disease as independent predictors of cardiovascular events. Among these, great emphasis has been placed on the role of vascular parameters assessed at the level of the carotid artery, such as Intima-Media Thickness (IMT). Poor data are available on the role of these markers as prognostic factors for Behçet's disease (BD). Objectives: The primary aim of this study was to explore Intima-Media-Thickness (IMT), mean arterial diameter and distensibility (DC) in a group of patients with BD; the secondary aim was to correlate the vascular parameters with demographic and clinical profile. Methods: Twenty-one BD patients (females/males: 7/14; mean age ± SD: 43±10.5; mean disease duration ± SD: 13±5.8) fulfilling the International Study Group (ISG) criteria were prospective enrolled. Demographic data, level of disease activity (BD activity index), frequency of smokers, previous history of diabetes mellitus, hypertension (defined as systolic blood pressure ≥140 mm Hg and diastolic blood pressure ≥90 mm Hg), family history of cardiovascular disease, body mass index (BMI) and current therapies were analysed. For each subject, ultrasound B-mode image sequences of right common carotid arteries were acquired and analysed by an automatic system (Carotid Studio, Quipu) for the measurement of IMT and mean arterial diameter. In addition, carotid pulse pressure (PP) was estimated by tonometry (Pulsepen, Diatecne) and DC coefficient was obtained. The systolic and diastolic carotid diameters were automatically measured on the distal wall of the common carotid artery, 1-2 cm beneath the bifurcation. Carotid diameter was calculated as the distance between media-adventitia interfaces. Cross-sectional distensibility coefficient (DC) was estimated through the variations in arterial cross-sectional area and blood pressure during systole. DC was computed as DC=ΔA/(PP*A) where A is the diastolic lumen area, ΔA is the stroke change in lumen area, and PP is the local pulse pressure. Results: At time of evaluation, 4 out of 17 patients presented active disease (50% ocular involvement, 25% joint involvement, 25% gastro-enteric involvement; mean BD activity score 5). Mean IMT ± SD value resulted of 0.57±0.81, mean arterial diameter ± SD value was 6.879±0.81 and mean DC ± SD 27.3±14.34. All the vascular parameters considered were significant correlated with BMI, while only IMT and DC were also significant correlated with arterial hypertension. Using a correction analysis for age and sex, we found significant correlations between mean arterial diameter and disease activity (p<0.0022) and between DC and disease duration. Conclusions: Our data have shown an interesting aspect, due to the influence that disease activity and duration of disease are on mean arterial diameter and DC, respectively. Although further data are necessary to confirm this hypothesis and since vascular parameters seem to reflect the status of disease activity, is desirable that future pharmacological researches target on this issue. Currently, we are performing a comparison with a disease control group of idiopathic inflammatory myopathies. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5146